Ensino de eletroquímica: célula A combustível confeccionada com materiais alternativos - SILVEIRA, Marlon Max Santos (2020)
This work was developed during the Professional Master's Program in Chemistry in National Network (PROFQUI) with the purpose of developing an educational product applicable to the content of electrochemistry in High School, prioritizing experimentation in teaching electrochemistry. The a research was carried out with two classes of the 2nd year of high school in a public school located in the interior of a state of Minas Gerais. The didactic sequence develops two experimental kits based on the fundamental concepts for the study of electrochemistry. The monitoring of learning assessments was based on the application of the pre-test as a parameter for comparing the knowledge acquired. The first experimental kit involves the production of hydrogen and oxygen gases from water electrolysis. The second experimental kit was based on the conversion of chemical energy into electrical energy from oxidation and reduction reactions of after hydrogen and oxygen gases respectively. The easy-to-build didactic experimental kits were made with alternative and easily accessible materials for use in common classrooms. Through the analysis of the student’s responses, it can be seen the experimental work developed using the kits favored the learning of the electrochemistry content in a more attractive way for the students. Throughout the activities developed, individual and collective learning of students was observed. The proposed activities were well accepted by students, increasing their interactivity and participation in classroom discussions.